Association of Nap Frequency With Hypertension or Ischemic Stroke Supported by Prospective Cohort Data and Mendelian Randomization in Predominantly Middle-Aged European Subjects - Yang, Min-Jing; Zhang, Zhong; Wang, Yi-Jing; Li, Jin-Chen; Guo, Qu-Lian; Chen, Xiang; Wang, E (Hypertension (Dallas, Tex. 1979), 2022)
The aim of this study was to investigate the association between daytime napping frequency and the incidence of essential hypertension or stroke as well as to validate causality in this relationship via Mendelian randomization (MR). We conducted Cox regression analysis on 358 451 participants free of hypertension or stroke from UK Biobank. To validate the results of the observational analysis, we conducted a 2-sample MR for daytime napping frequency (123 single-nucleotide polymorphisms) with essential hypertension in FinnGen Biobank, stroke, and ischemic stroke in MEGASTROKE consortium and performed a corresponding 1-sample MR on the UK Biobank data. Compared with never napping, usually napping was associated with a higher risk of essential hypertension (hazard ratio, 1.12 [95% CI, 1.08-1.17]), stroke (hazard ratio, 1.24 [95% CI, 1.10-1.39], and ischemic stroke (hazard ratio, 1.20 [95% CI, 1.05-1.36]) in our prospective observational analysis. Both the 1-sample and 2-sample MR results indicated that increased daytime napping frequency was likely to be a potential causal risk factor for essential hypertension in FinnGEN (odds ratio, 1.43 [95% CI, 1.06-1.92]) and UK Biobank (odds ratio, 1.40 [95% CI, 1.28-1.58]). The 2-sample MR results supported the potential causal effect of nap frequency on ischemic stroke in MEGASTROKE (odds ratio, 1.29 [95% CI, 1.04-1.62]). Prospective observational and MR analyses provided evidence that increased daytime nap frequency may represent a potential causal risk factor for essential hypertension. The potential causal association of increased nap frequency with ischemic stroke was supported by 2-sample MR and prospective observational results.